(untitled) (Nepal Journal of Obstetrics and Gynaecology, 2022)
Objectives: To assess the awareness and attitude regarding teenage pregnancy among adolescent girls. Methods: A descriptive cross- sectional design was carried out among 334 adolescent girls of school students of Chandannath Municipality, Jumla. Results: Awareness of teenage pregnancy was inadequate in 68% of adolescent girls, moderate in 26% and adequate in only 6%. Attitude to denounce teenage pregnancy was good in 58.1%, neutral in 34.4% and unfavorable in7.5%. There was no relation between awareness and attitude regarding teenage pregnancy and types of family, level of education of father and mother. Conclusion: Despite of favourable attitude against teenage pregnancy, the awareness level is low in adolescent girls. There was no significant difference between demographic variables with awareness and attitude regarding teenage pregnancy.